SISTEM INFORMASI AKUNTANSI KOPERASI SIMPAN PINJAM MENGGUNAKAN METODE CAMEL SEBAGAI ANALISIS TINGKAT KESEHATAN KOPERASI BERBASIS WEB (STUDI : KOPERASI SIMPAN PINJAM RACHMA JAYA SEMARANG) - Wulan Mahgfiroh (Universitas Sains dan Teknologi Komputer, 2018)
This study aims to determine the level of financial health in Rachma Jaya Savings and Loans cooperatives by using the CAMEL method of financial health research models that serve as benchmarks for cooperative inspection objects conducted by supervisors. The subjects in this study were the leadership of KOSPIN accounting department, the object of the research was analyzing financial statements such as the Profit and Loss report, Balance Sheet Reports, Cash Transaction Reports and Journals on KOSPIN during each period. This research is a type of descriptive research by means of which financial statements are used. For data collection techniques using documentation. Analysis of the data used is the CAMEL.CAMEL analysis itself consists of five criteria, namely Capital (Capital), Asset (Assets), Management (Management), Earning (Rentability), Liquidity (Liquidity). The results showed that the level of financial health that would indicate favorable or detrimental conditions for cooperatives. In this study, the results obtained in the 2017 period were 74.3. These results are in the numbers 60-80 on the accuracy of the predicate, so Rachma Jaya Semarang savings and loan cooperatives are included in the category HEALTHY ENOUGH. Then this indicator needs to be improved again so that all indicators on financial performance, especially those related to the level of health of the cooperative's financial well maintained.So this research resulted in Accounting Information System for Savings and Loans Cooperatives Using the Camel Method as a Health-Based Analysis of the Cooperative web-based (Case Study of Rachma Jaya Cooperative).